2014
DOI: 10.1007/s00018-014-1666-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional interplay between ATM/ATR-mediated DNA damage response and DNA repair pathways in oxidative stress

Abstract: To maintain genome stability, cells have evolved various DNA repair pathways to deal with oxidative DNA damage. DNA damage response (DDR) pathways, including ATM-Chk2 and ATR-Chk1 checkpoints, are also activated in oxidative stress to coordinate DNA repair, cell cycle progression, transcription, apoptosis, and senescence. Several studies demonstrate that DDR pathways can regulate DNA repair pathways. On the other hand, accumulating evidence suggests that DNA repair pathways may modulate DDR pathway activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
176
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 219 publications
(212 reference statements)
0
176
0
1
Order By: Relevance
“…This phosphorylation signaling is linked to formation of DSBs, but other types of DNA damage would also induce phosphorylation of these factors, for example oxidative DNA damage, formation of covalent DNA adducts, replication stress and SSBs. [62][63][64][65][66] This indicates that in latently infected cells, the DDR signaling pathway is activated in response to DNA damage suggesting that DNA repairs are not processed efficiently, or there is a factor raising the background level of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation signaling is linked to formation of DSBs, but other types of DNA damage would also induce phosphorylation of these factors, for example oxidative DNA damage, formation of covalent DNA adducts, replication stress and SSBs. [62][63][64][65][66] This indicates that in latently infected cells, the DDR signaling pathway is activated in response to DNA damage suggesting that DNA repairs are not processed efficiently, or there is a factor raising the background level of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…xidative stress is the imbalance between the production of reactive oxygen species (ROS) and antioxidant defenses (1,2). This presents a major challenge to genomic stability (3)(4)(5)(6) and is implicated in the pathogenesis of multiple human diseases, including cancer and neurodegenerative disorders (7,8).…”
mentioning
confidence: 99%
“…This presents a major challenge to genomic stability (3)(4)(5)(6) and is implicated in the pathogenesis of multiple human diseases, including cancer and neurodegenerative disorders (7,8). Abundant DNA damage from oxidative stress constitutes ∼10% of all DNA lesions and includes oxidative DNA damage, such as base damage, sugar moiety damage, apurinic/apyrimidinic (AP) sites, DNA single-strand breaks (SSBs), and double-strand breaks (DSBs) (2,6). Repair of oxidative lesions involves primarily the base excision repair (BER) pathway (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the prodrug scaffold is cleaved off during the conversion of precolibactin to colibactin [31,32]. Colibactin could act indirectly, for example, by inducing oxidative stress that triggers the release of free radicals reacting with DNA strands [33]. However, ROS are not immediately detected after infection, but rather a couple of days later [21], suggesting the early action of other factors, possibly nuclease(s).…”
Section: E Coli At the Gut Microbiota Scalementioning
confidence: 99%